2004
DOI: 10.1152/ajpregu.00508.2002
|View full text |Cite
|
Sign up to set email alerts
|

Feeding and temperature responses to intravenous leptin infusion are differential predictors of obesity in rats

Abstract: Obesity is frequently associated with leptin resistance. The present study investigated whether leptin resistance in rats is present before obesity develops, and thus could underlie obesity induced by 16 wk exposure to a liquid, palatable, high-energy diet (HED). Before HED exposure, male Wistar rats (weighing between 330 and 360 g) received intravenous infusions of 20 microg leptin 2 h before dark (approximately 57 microg/kg rat). Relative to saline infusion, this caused a highly variable effect on food intak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 40 publications
2
10
0
Order By: Relevance
“…There was, in fact, a slight decrease in the intake of chow (12% suppression relative to basal intake). This is consistent with one of our previous studies using the same paradigm, which finally led to an 82% increase in body weight relative to a group of rats that were left on chow (19). During the last week of HED exposure, rats were subjected to IVGTTs.…”
Section: Assessment Of Sensitivity To Mtii and Leptin And Their Relatsupporting
confidence: 91%
See 2 more Smart Citations
“…There was, in fact, a slight decrease in the intake of chow (12% suppression relative to basal intake). This is consistent with one of our previous studies using the same paradigm, which finally led to an 82% increase in body weight relative to a group of rats that were left on chow (19). During the last week of HED exposure, rats were subjected to IVGTTs.…”
Section: Assessment Of Sensitivity To Mtii and Leptin And Their Relatsupporting
confidence: 91%
“…This diet consisted of a 10% sucrose solution in which corn oil was emulsified. This diet was based on the work of Lucas and Sclafani (17) and Smith et al (18) and causes DIO in rats (19). The concentration of corn oil was doubled every 2 wk starting with 4% and finally ending up at 32% corn oil over the last weeks.…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…35 Rats that were relatively insensitive to leptin's anorexigenic effect were more prone to obesity when fed a high-fat diet. 36 Because leptin-sensitive neurons are also present in areas important for reward mechanisms, 31,32,37 it would be interesting to study whether the leptin sensitivity and the motivation to press for sucrose that both predict future obesity are related.…”
Section: Discussionmentioning
confidence: 99%
“…Selective breeding has shown that the DIO phenotype is not simply the result of a primary hyperphagia (45). Outbred DIO rats demonstrate reduced anorectic sensitivity to leptin (62,65) and to insulin (15). Studies with selectively bred DIO rats confirm the reduced leptin sensitivity (45) and suggest that this is a preexisting defect and not related to the reduction of leptin transport that occurs upon development of obesity.…”
mentioning
confidence: 96%